2015
DOI: 10.1186/s12862-015-0295-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth in fossil and extant deer and implications for body size and life history evolution

Abstract: BackgroundBody size variation within clades of mammals is widespread, but the developmental and life-history mechanisms by which this variation is achieved are poorly understood, especially in extinct forms. An illustrative case study is that of the dwarfed morphotypes of Candiacervus from the Pleistocene of Crete versus the giant deer Megaloceros giganteus, both in a clade together with Dama dama among extant species. Histological analyses of long bones and teeth in a phylogenetic context have been shown to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 57 publications
8
74
1
Order By: Relevance
“…Thin-sections were prepared following conventional procedure (Chinsamy-Turan, 2005;Kolb et al, 2015a;Padian and Lamm, 2013). The sections were taken as close as possible from the mid-diaphyseal level (see Appendix A for estimation of relative position of each thin-section).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thin-sections were prepared following conventional procedure (Chinsamy-Turan, 2005;Kolb et al, 2015a;Padian and Lamm, 2013). The sections were taken as close as possible from the mid-diaphyseal level (see Appendix A for estimation of relative position of each thin-section).…”
Section: Methodsmentioning
confidence: 99%
“…Our knowledge of the histology of the Cervidae (deer) was recently expanded with a work describing long bone and tooth histology of various taxa (Kolb et al, 2015a). Included in this study was the Miocene Procervulus, an early cervid whose growth rate was found to be especially low.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…An outer circumferential layer (OCL) (Ponton et al, 2004) consisting of avascular lamellar bone is present. The OCL indicates that, despite incompletely fused femoral epiphyses, the specimen reached skeletal maturity (Kolb et al, 2015a;Martinez-Maza et al, 2014). A minimum of three lines of arrested growth (LAGs) could be identified within the OCL (Figure 7.3).…”
Section: Bone Histologymentioning
confidence: 99%